Pengembangan Ekowisata Bantaran Sungai Gajah Wong Kapanewon Nologaten Kabupaten Sleman Yogyakarta - Saputro, Lilik Edi; Wardani, Dyah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study uses a qualitative approach with the aim of identifying the potential and challenges in the development of ecotourism on the banks of the Gajah Wong River, as well as formulating the right strategy in its management so that it can become a sustainable ecotourism destination. By focusing on the participation of local communities and the collaboration of various stakeholders, this research is expected to contribute to the development of ecotourism that supports the preservation of the local environment and culture. Ecotourism has a positive impact on the preservation of the local environment and indigenous culture, which is ultimately expected to be able to foster identity and pride among local residents through increased ecotourism activities. Kepanewon Nologaten, Caturtunggal which was previously known as a slum area has now been converted into an ecotourism area. It was concluded that the riverbank in Kepanewon nologaten, Sleman Regency, Yogyakarta has ecotourism potential that can be developed into an ecotourism destination.